Catching up to crypto : your guide to Bitcoin and the new digital economy - Armstrong, Ben (Investor) (Wiley, 2023)
"The economy is transitioning into digital currency as a means of transferring and processing transactions, but very little know about virtual currencies currently available. Bitcoin, a form of Cryptocurrency for virtual transfers and transactions, is becoming well known not only within businesses but also everyday users. Bitcoin encourages users to use as a transfer method of money in a safe and efficient way. Users have access to use Bitcoin without qualification, except that one uses a computer or device for processing. No central banks, authority, of governments have involvement in monitoring Bitcoin exchanges, as no third party is involved with Bitcoin increasing independence for its users. With no regulating of ones Bitcoins, users have the advantage of freely processing payments using Bitcoin, even from Country to Country as long as it is accepted as a form of payment or exchange in that Country."--